Genome-Wide Identification of ATL Gene Family in Wheat and Their Expression Analysis in Response to Salt Stress - Xuqing Li; Shuotong Liu; Pei Yu (Plants)
Wheat (Triticum aestivum) is one of the most important cereal crops globally, with significant economic value. The Arabidopsis Tóxicos en Levadura (ATL) gene family, which comprises members of ubiquitin ligase enzymes (E3s), functions in substrate protein tagging during ubiquitin-mediated protein modification. Recent studies have demonstrated its involvement in stress responses. However, the ATL gene family in wheat remains poorly characterized. This study aimed to identify the members of the ATL gene family in wheat and investigate their roles under salt stress. We identified 334 TaATL genes in the wheat genome, all of which contain either RING-H2, RING U-box, or RAD18 superfamily domains, exhibiting a remarkably low proportion of intron-containing genes. The Ka/Ks (non-synonymous to synonymous substitution rate) analysis and cis-acting element analysis of the TaATL gene family indicate that its sequences are highly conserved and functionally constrained, suggesting that it may participate in abiotic stress responses through the ABA, MeJA, and MYB signaling pathways. Both RNA-seq analysis and RT-qPCR data demonstrated that the expression levels of the TaATL gene family were significantly upregulated under stress conditions, indicating their crucial roles in stress responses. This study demonstrates that the targeted regulation of stress-responsive signaling pathways mediated by superior TaATL gene family members can effectively enhance wheat salt tolerance, thereby providing a viable strategy for the development of high-yielding cultivars adapted to saline agricultural ecosystems.